Re-boosting Mass and Ecotourism in Lombok, Indonesia, Post COVID-19:: Opportunities, Challenges and Strategic Pathways - Wahyudi, Fendy Eko; Susiatiningsih, Hermini; Suwarno, Peter (Journal of Mandalika Review, 2026)
Introduction: This study examines the re-boost strategies for the tourism sector of Lombok, Indonesia, in the aftermath of the COVID-19 pandemic, with particular emphasis on the synergistic and sometimes conflicting domains of mass tourism and ecotourism. Methodology: Drawing on extant literature, policy documents, and qualitative data derived from interviews with local stakeholders, this paper explores how Lombok’s tourism industry can navigate post-pandemic challenges—health protocols, visitor hesitancy, environmental sustainability concerns, and socio-economic setbacks—while capitalizing on new opportunities. Findings: Lombok’s tourism landscape stands at a crossroads. The COVID-19 pandemic brought new opportunities for mass and eco-tourism-related business in Lombok, to adjust with the growing importance of tourist new preferences. Though cultural and ecological preservation efforts are mainly driven by non-governmental organizations and local communities, several local businesses and authorities has adjusted their strategies to integrate with the post-pandemic recovery efforts—highlighted multi-stakeholder approaches. Conclusion: The article concludes that significant growth of post-pandemic tourists centered adjustment driven by local authorities and communities must be guided with policy recommendations and community-based strategies that aim to strengthen Lombok’s position as a leading destination for both mass and ecotourism.